Radical Cystectomy Against Intravesical BCG for High-Risk High-Grade Nonmuscle Invasive Bladder Cancer: Results From the Randomized Controlled BRAVO-Feasibility Study. Issue 3 (20th January 2021) - Catto, James W. F.; Gordon, Kathryn; Collinson, Michelle; Poad, Heather; Twiddy, Maureen; Johnson, Mark; Jain, Sunjay; Chahal, Rohit; Simms, Matt; Dooldeniya, Mohantha; Bell, Richard; Koenig, Phillip; et al.
Abstract : PURPOSE: High-grade nonmuscle invasive bladder cancer (HRNMIBC) is a heterogeneous disease. Treatments include intravesical maintenance Bacillus Calmette-Guerin (mBCG) and radical cystectomy (RC). We wanted to understand whether a randomized trial comparing these options was possible. MATERIALS AND METHODS: We conducted a two-arm, prospective multicenter randomized study to determine the feasibility in Bacillus Calmette-Guerin -naive patients. Participants had new high-risk HRNMIBC suitable for both treatments. Random assignment was stratified by age, sex, center, stage, presence of carcinoma in situ, and prior low-risk bladder cancer. Qualitative work investigated how to maintain equipoise. The primary outcome was the number of patients screened, eligible, recruited, and randomly assigned. RESULTS: We screened 407 patients, approached 185, and obtained consent from 51 (27.6%) patients. Of these, one did not proceed and therefore 50 were randomly assigned (1:1). In the mBCG arm, 23/25 (92.0%) patients received mBCG, four had nonmuscle invasive bladder cancer (NMIBC) after induction, three had NMIBC at 4 months, and four received RC. At closure, two patients had metastatic BC. In the RC arm, 20 (80.0%) participants received cystectomy, including five (25.0%) with no tumor, 13 (65.0%) with HRNMIBC, and two (10.0%) with muscle invasion in their specimen. At follow-up, all patients in the RC arm were free of disease. Adverse events were mostly mild and equally distributed (15/23 [65.2%] patients with mBCG and 13/20 [65.0%] patients with RC). The quality of life (QOL) of both arms was broadly similar at 12 months. CONCLUSION: A randomized controlled trial comparing mBCG and RC will be challenging to recruit into. Around 10% of patients with high-risk HRNMIBC have a lethal disease and may be better treated by primary radical treatment. Conversely, many are suitable for bladder preservation and may maintain their prediagnosis QOL.